UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN KEMANGI (Ocimumbasilicum L.) TERHADAP PERTUMBUHAN BAKTERI Staphylococcusaureus - Manurung, Kesaktian; Marpaung, Jon Kenedy; Harefa, Karnerius; Mardianis, Mardianis (UNIVERSITAS SARI MUTIARA INDONESIA, 2021)
Basil (Ocimumbasilicum L.) is one of the natural plants that is easily obtained in Asia such as Indonesia which has medicinal properties. Basil leaves contain flavonoid compounds, tannins, saponins, and steroids/triterpenoids. These compounds are known to have antibacterial activity. This study aims to determine the antibacterial activity of the ethanolic extract of basil leaves (Ocimumbasilicum L.) against Staphylococcus aureus bacteria. This research is experimental. The test was carried out through several stages including material collection, preparation of simplicia, making ethanol extract of basil leaves, and testing the inhibitory power of basil leaves against Staphylococcus aureus bacteria. The ethanol extract of basil leaves was made by the maceration method using 96% ethanol and concentrated with a rotary evaporator to obtain a thick extract from basil leaves. Antibacterial activity was tested by the agar diffusion method using disc paper. The results of the antibacterial activity test showed that the ethanolic extract of basil leaves inhibited the growth of Staphylococcus aureus bacteria at concentrations of extracts of 5%, 10%, 15%, 20%, and 25% with inhibition zone diameters of 8. 31 mm, 9. 43 mm, respectively. 9. 73 mm, 9. 91 mm, and 11. 33 mm. The ethanol extract of basil leaves has antibacterial activity against Staphylococcus aureus bacteria.